2018
DOI: 10.23889/ijpds.v3i1.445
|View full text |Cite
|
Sign up to set email alerts
|

Coding reliability and agreement of international classification of disease, 10th revision (ICD-10) codes in emergency department data

Abstract: IntroductionAdministrative health data from emergency departments play important roles in understanding health needs of the public and reasons for health care resource use. International Classification of Disease (ICD) diagnostic codes have been widely used to code reasons of clinical encounters for administrative purposes in emergency departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…This includes records with missing diagnoses, and variation of coding amongst care providers. Peng et al (2018) [54] found overall agreement (82.2%) and reliability (0.82) among 11 hospitals in emergency department ICD-10 (4-digits level) codes. Also, in this work the first 4 out of possible 14 (ICD-10) diagnoses codes in the PEDW dataset were used because in a previous study it was found the most optimal set of codes for similar analyses of alcohol-related emergency admissions for adults [33].…”
Section: Discussionmentioning
confidence: 99%
“…This includes records with missing diagnoses, and variation of coding amongst care providers. Peng et al (2018) [54] found overall agreement (82.2%) and reliability (0.82) among 11 hospitals in emergency department ICD-10 (4-digits level) codes. Also, in this work the first 4 out of possible 14 (ICD-10) diagnoses codes in the PEDW dataset were used because in a previous study it was found the most optimal set of codes for similar analyses of alcohol-related emergency admissions for adults [33].…”
Section: Discussionmentioning
confidence: 99%
“…Routinely collected electronic hospital records were used in this work, which were recorded in different hospitals and by different coders. Peng et al (2018) [ 39 ] showed overall agreement (82.2%) and reliability (0.82) among 11 hospitals in emergency department ICD-10 (4-digits level) diagnostic codes. No influence of coder characteristics was found in almost half million ICD-10 hospital discharge records [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent Canadian research assessing quality of ICD10 coding in ED records concluded that diagnoses codes showed high agreement and reliability, although variations were observed across hospitals. 23…”
Section: Discussionmentioning
confidence: 99%